Shrinkage parameters of modified compacted clayey soil for sustainable earthworks - Onyelowe, Kennedy C.; Onyia, Michael E.; Duc, Bui Van; Firoozi, Ali A.; Uche, Okorie A.; Kumari, Seema; Oyagbola, Ismail; Amhadi, Talal; Lam, Dao-Phuc (Penerbit Universiti Kebangsaan Malaysia, 2021)
The shrinkage limit is one of the Atterberg limits and is a fundamental geotechnical parameter used to assess the settlement and other volume change parameters of engineering soils containing clays. This paper describes shrinkage limits and index tests results on expansive soil treated with rice husk ash (RHA) and 5%, 10% and 15% quicklime activated rice husk ash (QARHA) obtained using laboratory testing procedure. The representative soil was subjected to classification tests and it was found to be high expansive soil, an A-7-6 soil according to American Association of States Highway and Transportation Officials (AASHTO) and poorly graded according to Universal Soil Classification System (USCS). It was classified as highly plastic soil. The soil was subjected to treatment exercise at the rate of 0% (reference), 2%, 4%, 6%, 8% and 10% addition of RHA, 5%-QARHA, 10%-QARHA and 15%-QARHA by weight of dry soil. The RHA addition improved the shrinkage properties; shrinkage limit at varying rates ranging from 5.7%, to 27.9% for 2%, and 10% RHA addition respectively with reference to the control experiment. And for the shrinkage index, the improvement rate was also substantial i.e. 7.8% to 55.7% at 2% and 10% RHA addition respectively with reference to the control experiment. The effect of rice husk ash activated with 5% quicklime lime (5%-QARHA) showed improvement rate of 6.6% and 34.4% at 2% and 10% 5%-QARHA addition respectively with reference to the control experiment. Also, the effect of rice husk ash activated by 10% and 15% quicklime (10%-QARHA and 15%-QARHA) on the shrinkage properties was presented with the rates of improvement which shows that the higher the rate of activation of rice husk ash with quicklime, the higher the pozzolanic performance Finally, rice husk ash and its composites achieved by quicklime activation process have shown to be alternative cementing materials for use as binders in the modification of expansive soils utilized as subgrade materials.